2022
DOI: 10.1097/ee9.0000000000000194
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to metal mixtures and newborn neurobehavior in the Rhode Island Child Health Study

Abstract: In this study, we utilize placenta as a biomarker for prenatal metal exposure and evaluate whether metal mixture is linked to newborn neurobehavioral performance assessed using the NNNS. This approach and topic make this manuscript of interest to the audience of Environmental Epidemiology, and this manuscript represents the first to link an examination of a mixture of metal exposure and early life measures of neurobehavioral development. Findings from this study may shed insight on developing useful policies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 77 publications
1
3
1
Order By: Relevance
“…The absence of a statistically significant association between the older age of pregnant women and a higher risk of exposure to mixed heavy metal contaminations noted in the current study is not in agreement with the results from previous studies [46][47][48]. For instance, in a Chinese investigation that specifically explored the occurrence of heavy metals in different age groups, higher concentrations were found in middle-aged women when compared to younger women [64].…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…The absence of a statistically significant association between the older age of pregnant women and a higher risk of exposure to mixed heavy metal contaminations noted in the current study is not in agreement with the results from previous studies [46][47][48]. For instance, in a Chinese investigation that specifically explored the occurrence of heavy metals in different age groups, higher concentrations were found in middle-aged women when compared to younger women [64].…”
Section: Discussioncontrasting
confidence: 96%
“…The simultaneous exposure to two or three heavy metals at levels above recommended public health action levels-including mercury, manganese, and lead-has been reported before in, among others, Japan [46], the USA [47], and China [29]. In line with the results from the current study, the investigators suggested that education and low income might represent potential risk factors for exposure to multiple contaminants [46,48].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Authors reported some longterm deleterious effects of two neurotoxic metals (Hg and Pb) and two micronutrients (Zn and Se) on child behavior and IQ. A recent multi-element analysis performed in the US Rhode Island Child Health Study (n = 192) found a positive association (worse tests results) between increased levels of a mixture of placental metals (Cd, Co, Cu, Fe, Mn, Mo, Se and Zn) and atypical behavior in newborns (Tung et al 2022), with Cd having the largest weight in the mixture effect.…”
Section: Resultsmentioning
confidence: 99%
“…In the second stage, we assessed the associations of air pollutant mixtures with allcause and cause-specific AECs by conducting quantile g-computation models. Quantile g-computation has been regarded as a simple and efficient statistical method for evaluating the combined effect of air pollutant mixtures when all pollutants simultaneously increase each quantile, which allows the combined air pollutants to present positive, negative, and null effects simultaneously [18,19]. In this study, we implemented this model by categorizing PM 2.5 , PM 10 , Ozone, NO 2 , and SO 2 into quantiles, coded as 0, 1, 2, 3, and 4, respectively.…”
Section: Discussionmentioning
confidence: 99%